IMPROVING REGIONAL MANAGEMENT AND IMPLEMENTATION MECHANISMS TO INCREASE TOURISM EFFICIENCY - Toshev, Nurbek Janon oglu (THE INNOVATION ECONOMY, 2026)
This article examines the issues of improving regional management and implementation mechanisms in increasing tourism efficiency. The study analyzes the institutional and organizational-economic aspects of tourism development. The main factors affecting efficiency at the regional level are identified. Ways to effectively use resources and improve the quality of services in tourism are substantiated. As a result, the need for an integrated approach to regional management is demonstrated.